Directness and Dignity in EFL Speaking Feedback: Students’ Confidence Trajectories - Amra Ariyani; Muhammad Arham (Tamaddun Life, 2026)
Oral corrective feedback is essential in English as a foreign language (EFL) speaking instruction, yet feedback that students experience as unusually firm, harsh, or direct may create a tension between linguistic improvement and confidence. This qualitative study examined how EFL undergraduates perceived strong lecturer feedback, how it influenced their confidence and participation immediately and over time, and which delivery conditions shaped constructive or harmful outcomes. Data were analyzed using reflexive thematic analysis. Four themes were developed: (1) directness is not the same as harshness; (2) the evaluative spotlight produces an immediate affective shock; (3) one feedback event can fork into productive vigilance or protective silence; and (4) students want clarity with dignity and a usable next step. Public correction frequently generated embarrassment, anxiety, and an immediate decline in confidence. However, longer-term responses diverged. Some students converted discomfort into greater preparation, pronunciation, and grammar practice, and eventual confidence recovery, whereas others reduced volunteering, became quieter, or participated only when they felt safe. Clear correction was often welcomed when it was respectful, specific, and actionable; perceived humiliation was associated more strongly with tone, interruption, judgmental wording, and public exposure than with directness itself. The findings show that strong feedback does not have a uniformly negative influence. Its effect is appraisal-mediated and relational, depending on how learners interpret the lecturer's intent, preserve social dignity, and identify a feasible route for improvement. The study recommends confidence-preserving directness rather than either harshness or vague praise.